Przekład w dziele poety - Zaleski, Marek (Śląskie Studia Polonistyczne, 2014)
In the review of a book Goliwość tłumacza. Przekład poetycki w twórczości Czesława Miłosza (Kraków, 2013) by Magda Heydel, the author finds an example of great application of the latest in translation studies theories. Miłosz’s translator activity turned out to be a very graceful subject for deliberation, since the poet as a translator did not see his role as a neutral intermediary, but rather executed his own literary project – an idea of a modern silva rerum, crossing genre, stylistic, and cultural boundaries.